Language distribution in Nepal and question on unit of additional official language - Regmi, Bhim Narayan (Gipan, 2019)
Nepal has 123 languages within six families of spoken languages and a sign language. She has federal administrative structure and three levels of government. There is no majority language at national level. Nepali is the only majority language at province level with majority in 4 among the 7 provinces, and 21 majority languages at local level. The distribution of languages in terms of mother tongue speakers varies considerably among the different levels – national, province and local – as well as among the different units of the same level – among the provinces and among the local levels. According to the provision in the prevalent constitution, one or more majority language(s) spoken as mother tongue in a province can be additional official language of the province provided by the particular province through province law. This paper looks at the language data at different levels and concludes that the province is not the appropriate unit for use of additional official language in terms of cost effectiveness and inclusiveness, instead local level is the appropriate unit. Thus it suggests to consider local level as the unit of implementation and include the languages above 25% mother tongue speakers in the local level for the additional official language.